Measuring change attitudes in health care organizations - Hower, Kira Isabel; Pfaff, Holger; Kowalski, Christoph; Wensing, Michel; Ansmann, Lena (Journal of health organization and management, 2019)
Purpose Measuring attitudes of healthcare providers and managers toward change in health care organizations (HCOs) has been of widespread interest. The purpose of this paper is to evaluate the psychometric characteristics and usability of an abbreviated German version of the Change Attitude Scale. Design/methodology/approach The Change Attitude Scale was used in a survey of healthcare providers and managers in German hospitals after the implementation of a breast cancer center concept. Reliability analysis, confirmatory factor analysis, structural equation modeling and bivariate analysis were conducted. Findings Data from 191 key persons in 82 hospitals were analyzed. The item-scale structure produced an acceptable model fit. Convergent validity was shown by significant correlations with measures of individuals’ general opinions of the breast center concept. A non-significant correlation with a scale measuring the hospital’s hierarchical structure of leadership verified discriminant validity. The interaction of key persons’ change attitude and hospitals’ change performance through change culture as a mediator supported the predictive validity. Research limitations/implications The study found general support for the validity and usability of a short version of the German Change Attitude Scale. Practical implications Since attitudes toward change influence successful implementation, the survey may be used to tailor the design of implementation programs and to create a sustainable culture of high readiness for change. Originality/value This is the first study finding that a short instrument can be used to measure attitudes toward change among healthcare providers and managers in HCOs.